Flooding away the economic gains from transport infrastructure: Evidence from colonial Jamaica - Joel Huesler; Eric Strobl (European Historical Economics Society (EHES), 2024)
We investigate how the frequent flooding that damaged the internal transport infrastructure in late 19th and early 20th colonial Jamaica affected local economies. To this end the evolution of the road and railways transport system was geo-referenced and combined with geo-localized damaging flood events, as well as with information on local economic activity proxied by internal tax revenue. Econometric analysis on our 30 year parish level time varying data set shows that lower market access from the flood disruptions to transport reduced tax revenue on average by 3.5%, and during some incidences up to 9.1%, over its two year impact. Decomposing the tax data by source suggests that both the property and the non-agricultural service sectors suffered after damaging floods. In contrast, flood disruptions benefited the agricultural sector, although only agricultural traders and not producers appear to have gained from investments in the transport network in general.
Keywords: Q54; R00; 330; Transportation Network; Flooding; Market Access; Regional Economics; Jamaica